2012
DOI: 10.1021/nl3020022
|View full text |Cite
|
Sign up to set email alerts
|

Screening-Engineered Field-Effect Solar Cells

Abstract: Photovoltaics (PV) are a promising source of clean renewable energy, but current technologies face a cost-to-efficiency trade-off that has slowed widespread implementation. We have developed a PV architecture-screening-engineered field-effect photovoltaics (SFPV)-that in principle enables fabrication of low-cost, high efficiency PV from virtually any semiconductor, including the promising but hard-to-dope metal oxides, sulfides, and phosphides. Prototype SFPV devices have been constructed and are found to oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 23 publications
1
38
0
1
Order By: Relevance
“…Studies on semi-transparent photovoltaics have also been conducted [28,103,[111][112][113][114][115], likewise life cycle assessments (LCA) of photovoltaics [20,55,116,117]. Furthermore, note the study of screening-engineered field-effect solar cells by Regan et al [118]. Other relevant studies on BIPV may also be found in the scientific literature [119][120][121][122][123][124][125][126][127][128].…”
Section: Various Aspectsmentioning
confidence: 99%
“…Studies on semi-transparent photovoltaics have also been conducted [28,103,[111][112][113][114][115], likewise life cycle assessments (LCA) of photovoltaics [20,55,116,117]. Furthermore, note the study of screening-engineered field-effect solar cells by Regan et al [118]. Other relevant studies on BIPV may also be found in the scientific literature [119][120][121][122][123][124][125][126][127][128].…”
Section: Various Aspectsmentioning
confidence: 99%
“…In 2012, Regan et al demonstrated field‐effect SCs, using a transparent top gate to regulate the potential barrier and the electric field in a metal‐semiconductor junction for the purpose of separating photo generated electron‐hole pairs 80. Zettl et al presented a new type of field‐effect SC utilizing graphene and zinc phosphide (Zn 3 P 2 ) to form a tunable junction barrier thin‐film light absorber 81.…”
Section: The Human‐like Senses and Feedbacksmentioning
confidence: 99%
“…Under this reasonable (but not always true [65]) limit, the total areal charge summed over both electrodes must be equal and opposite to the total charge within the active layer, or…”
Section: F Areal Charge Densities On the Contactsmentioning
confidence: 99%